Education on Good and Correct Waste Sorting in Permata Cikarang Housing Block S RT.06 RW.12 Cikarang Timur District Bekasi - West Java - Supini; Atmaja, Surya Jaya; Andi Widi Santoso; Topan; Bahrun; Abdullah; Lilik Sukandar; Sri Ayu Gerana Wulan; Tri Yuyun Muslihat; Lina Susilawati; Tiyani; Silvia Hilwiatun Nisvi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service activity focuses on socialization and education on good and correct waste sorting practices to increase public awareness about environmental conservation. This program was implemented at the Permata Cikarang Blok iS housing complex, involving residents from various backgrounds. This activity includes interactive presentations, as well as the distribution of information material. The results of the activity show an increase in participants' understanding of the importance of waste management, as well as a commitment to applying this knowledge in everyday life. This initiative emphasizes the role of education in encouraging sustainable environmental practices and reducing problems related to community waste.